Changes of Form of Malay Traditional Houses in Medan and Surroundings - Imam Faisal Pane; Hilma Tamiami Fachrudin (Britain International for Academic Research (BIAR) Publisher, 2020)
Malay Architecture is one of the architectures that developed in Medan City and its surroundings. Malay ethnicity has existed and developed in this area marked by the presence of the Deli Malay Sultanate whose Kingdom capital is in Medan. With the existence of this Sultanate, the existence of Malay architecture is getting stronger and influencing the community, especially for the Malay community. This article aims to look at the development of Malay architecture nowadays with various influences that come from everywhere. This influence is certainly related to the form of this building which changes follow the times. Observation locations are in Medan and its surrounding areas, namely Langkat and Serdang Bedagai. Qualitative methods are used to see physical facts in the field which are corroborated by the questionnaire as a form of respondents’ expressions. The results obtained are some changes to the building caused by the variety of activities owned by residents of the house so that it requires space that affect the changes in the form and function of the building. Overall, the building owner still maintains the characteristics of Malay traditional architecture, especially the use of ornaments or decoration on the building.